(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to analyze and obtain empirical evidence knowing the exact time to be predicted determining the reversal date of the JCI (Jakarta Composite Index) price and Gold prices can use the method of Astrology, Fibonacci, Astronacci. The method used in this research is descriptive and explanatory methods. Descriptive method is used to make steps Astrology, Fibonacci, and Astronacci methods to find the reversal date of the JCI and the price of Gold in the future. While the explanatory method is used to apply Astrology, Fibonacci, and Astronacci methods using historical data (in 2008-2017), JCI and Gold prices. Data used in this study for 1 decade is January 1, 2008 to December 31, 2017. Based on the three methods, the reversal opportunity of both the JCI and the highest Gold price using the Astronacci method rather than astrology or Fibonacci alone.